2020
DOI: 10.1002/lio2.497
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter survey on the effectiveness of nasal irrigation devices in rhinosinusitis patients

Abstract: Background: Nasal irrigation is widely used as an adjunctive treatment for rhinosinusitis. However, there is little information available regarding the efficacy of the devices used in this procedure. The objective of this study was thus to evaluate the effectiveness of nasal irrigation devices based on the experiences of patients with rhinosinusitis. Methods: We conducted a multicenter survey study between November 2017 and December 2019. The questionnaire was developed based on the available literature and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…21 In a recent survey of 129 acute rhinosinusitis patients, the patients reported that large-volume, positivepressure devices help clear secretion more effectively than low-volume devices. 5 The present study was designed to assess patients with ARS which included all ARS subtypes (common cold, postviral rhinosinusitis, and ABRS). These subtypes are different in pathogenesis, clinical symptoms, disease onset, and duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21 In a recent survey of 129 acute rhinosinusitis patients, the patients reported that large-volume, positivepressure devices help clear secretion more effectively than low-volume devices. 5 The present study was designed to assess patients with ARS which included all ARS subtypes (common cold, postviral rhinosinusitis, and ABRS). These subtypes are different in pathogenesis, clinical symptoms, disease onset, and duration.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of large volume, positive pressure saline irrigation is to mechanically wash nasal discharge out of the nasal cavity 21 . In a recent survey of 129 acute rhinosinusitis patients, the patients reported that large‐volume, positive‐pressure devices help clear secretion more effectively than low‐volume devices 5 . The present study was designed to assess patients with ARS which included all ARS subtypes (common cold, postviral rhinosinusitis, and ABRS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the international consensus statement of allergy and rhinology: rhinosinusitis in 2016, it is strongly recommended that large volume (>200 mL) nasal saline irrigation be used as an auxiliary means for other drug treatment of CRS [ 86 ]. A recent study involving 418 patients with rhinosinusitis showed that large-volume nasal irrigators were more effective than other types of irrigators in removing nasal secretions and reducing postnasal drip [ 87 ]. Kanjanawasee et al [ 88 ] compared the effects of nasal irrigation using hypertonic saline (HS) and isotonic saline (IS) in treating sinonasal diseases.…”
Section: Methods Of Nasal Drug Deliverymentioning
confidence: 99%